Biolinguistics and the Implication for Teaching Language on Young Learners - Abbas Achmad Badib (TEFLIN, 1998)
Abstract: The majority of foreign language teachers tend to believe that there is a significant different approach in terms of a teaching strategy dealing with the first and second language instructions. Can those different approaches be substantiated by our sound justificaÃÂtions based on our proper understanding and essential knowledge of language processes? Generally speaking, our understanding of the nature of language acquisition in terms of biolinguistics is only parÃÂtial. Therefore, this paper attempts to explore the biological aspects of the process of language acquisition by a child and then compare it with the developments of the birth of language. In other words this paper will examine very briefly the micro and macro evolutions of language. Central to this discussion are the neurological developÃÂments in the brain, which are responsible for language planning and the speech apparatus responsible for language productions. By exÃÂamining the two related activities, we can then study how language is actually carried out by human beings, both first and second language acquisitions. After developing a proper understanding of the bioÃÂlogical aspects of language, we can thus explore further the best way of language processes. This may constitute a new insight of lanÃÂguage teaching because so far, relying on linguistic theories alone, it is often difficult to obtain the most acceptable information regarding the nature of first and second language teaching.